Teacher’s Beliefs and Practices in the Integration of Higher Order Thinking Skills in Teaching Reading - Muhammad Ansori; Joko Nurkamto; Suparno Suparno (ELS Journal on Interdisciplinary Studies in Humanities, 2019)
Higher Order Thinking Skills (HOTS) is an essential skill for students to compete in this technological age. Hence, teachers need to hold strong beliefs about HOTS as it influences their classroom practices. Moreover, the study about HOTS in English language teaching has not been widely explored. This case study seeks to explore teacher’s beliefs in the integration of HOTS in teaching reading and how the beliefs are reflected in classroom practices. Further, it also investigates the factor influencing the teacher’s beliefs and practices. The participant was an experienced English teacher in a public senior high school. Data were collected using interviews, observation, and review of documents. Data then were analyzed using the Pattern Matching technique (Yin, 2018) and interactive model data analysis (Miles, Huberman, & Saldaña, 2014). The results revealed that the teacher held strong beliefs about the integration of HOTS in teaching reading. These beliefs include belief about the conception of HOTS, the importance of HOTS, the role of the teacher, the strategies to promote HOTS, and the assessment of HOTS. In practice, the teacher did not fully reflect what she believes, especially about the assessment of HOTS. It also found that training, learning experience, teaching experience, institutional factor, student factor, and availability of learning support influenced teacher beliefs and practice in integrating HOTS in teaching reading. This study implies that there needs more teachers’ professional development to support the successful integration of HOTS in English language teaching.